LOOKING INSIDE LATE VARISCAN TECTONICS: STRUCTURAL AND METAMORPHIC HETEROGENEITY OF THE EASTERN SOUTHALPINE BASEMENT (NE ITALY) - Benciolini L.; Poli M.E.; Zanferrari A.; Visonà D. (My University, 2006)
The Eastern Southalpine Basement on the southern side of the Brixen granodiorite pluton is comprised of two rock volumes separated by a shear zone and characterised by contrasting thermo-mechanical evolutions. The first rock volume appears in three different areas within hectometric folds consisting of amphibolite-facies paragneiss with polyphase structural and metamorphic evolution: a) D1 developed in HT-MP conditions: The assemblage Qtz + Pl + Bt + Kfs + Grt assemblage is preserved within D1 microlithons; b) D2 is recorded in HT-LP conditions. Assemblages Bt + And + Crd, and Qtz + Kfs + Sil + Pl + Crn, developed within the differentiated S2 layering; c) D3 developed in greenschist-facies, characterized by assemblage Ser + Qtz + Chl + Ab; d) the contact aureole of the Brixen granodiorite pluton generating static growth of biotite, andalusite II and cordierite II at 282 ±14 Ma. The second rock volume corresponds to the Brixen - Sarntal metamorphic basement described in the literature, and consists of greenschist-facies metapelite. Field relationships indicate that HT-LP metamorphism took place before emplacement of the Brixen granodiorite and that paragneiss and metapelite were probably coupled at 320Ma, whereas the metamorphic aureole statically overprints the dynamic events and seals the contact. © 2006 Lavoisier SAS. All rights reserved.
Keywords: EASTERN SOUTHERN ALPS; OROGENIC COLLAPSE; VARISCAN OROGENY